An Overview of the Stages (Heuristics) Model as a Public Policy Analysis Framework - Kulaç, Onur; Özgür, Hüseyin (European Scientific Journal, ESJ, 2017)
Public policy analysis requires a comprehensive research and a framework in order to figure out the details of the policies applied. Thus, many public policy analysis models are used in various policy fields so as to examine the all stages of the public policy making and implementation process. Stages model is one of the most well-known and the oldest policy analysis frameworks that have been used by many policy analysts, academicians and independent researchers around the world. In this paper, firstly, the background of the stages model and its development process will be briefly dealt. Later on, the main advantages of the stages model will be put forth by comparing with other common public policy analysis models. Lastly, examples of the public policy analyses that stages model was taken as a main analysis framework in different policy fields and countries will be scrutinised. This paper reveals that the stages model is a suitable, easily applicable, efficient, attractive, and usable framework in analysis of public policies.